2015
DOI: 10.1371/journal.pone.0134531
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Hepatic Steatosis Are Associated with Elevated Serum Amyloid Beta in Metabolically Stressed APPswe/PS1dE9 Mice

Abstract: Diabesity-associated metabolic stresses modulate the development of Alzheimer’s disease (AD). For further insights into the underlying mechanisms, we examine whether the genetic background of APPswe/PS1dE9 at the prodromal stage of AD affects peripheral metabolism in the context of diabesity. We characterized APPswe/PS1dE9 transgenic mice treated with a combination of high-fat diet with streptozotocin (HFSTZ) in the early stage of AD. HFSTZ-treated APPswe/PS1dE9 transgenic mice exhibited worse metabolic stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
(32 reference statements)
3
20
0
Order By: Relevance
“…Similar results were obtained following induction of diabetes by β‐cell ablation with streptozotocin in conjunction with high‐fat feeding in APP(SWE)/PSEN1dE9 mice . In this study, circulating Aβ levels were significantly correlated with body weight gain, blood glucose and hepatic triglyceride content . Similarly, genetic susceptibility to metabolic disease is exaggerated with elevated amyloidogenic APP processing.…”
Section: An Integrated Model For Metabolic Regulation By App/app Peptsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar results were obtained following induction of diabetes by β‐cell ablation with streptozotocin in conjunction with high‐fat feeding in APP(SWE)/PSEN1dE9 mice . In this study, circulating Aβ levels were significantly correlated with body weight gain, blood glucose and hepatic triglyceride content . Similarly, genetic susceptibility to metabolic disease is exaggerated with elevated amyloidogenic APP processing.…”
Section: An Integrated Model For Metabolic Regulation By App/app Peptsupporting
confidence: 83%
“…For example, APP(SWE)/PSEN1(A246E) mice, comprising an AD mouse model with elevated systemic levels of Aβ, are more susceptible to high‐fat diet‐induced weight gain, hyperglycaemia and glucose intolerance . Similar results were obtained following induction of diabetes by β‐cell ablation with streptozotocin in conjunction with high‐fat feeding in APP(SWE)/PSEN1dE9 mice . In this study, circulating Aβ levels were significantly correlated with body weight gain, blood glucose and hepatic triglyceride content .…”
Section: An Integrated Model For Metabolic Regulation By App/app Peptsupporting
confidence: 76%
“…Diet-induced peripheral metabolic changes have been suggested to be linked with amyloidosis [ 18 ]. Previously, we created an HFSTZ APP/PS1 animal model, which displayed diabesity and hepatic steatosis; elevated peripheral Aβ level; enhanced Aβ level, plaque burden, astrocyte activation, vascular inflammation, glucose hypometabolism in the cerebrum, and caused cognitive impairment in APP/PS1 mice [ 3 , 4 ]. In the present study, the effects of APS on the pathological changes stated above were studied.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we found that obesity, hyperglycemia, hepatic steatosis, Aβ plaque burdens and cerebrovascular inflammation in APPswe/PS1ΔE9 (APP/PS1) transgenic mice is accelerated by the combination of high-fat diet (HFD) and a low-dose injection of streptozotocin (STZ) (i.e., HFSTZ AD mice) [ 3 , 4 , 5 ]. In those studies, we found an interplay between genetic background of AD and HFSTZ-induced metabolic stress.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a number of AD animal models with increased circulating Aβ levels are reported to recapitulate aspects of the metabolic disturbances seen in obesity and type 2 diabetes. These include insulin resistance, glucose tolerance and dyslipidaemia (Mody et al 2011, Jimenez-Palomares et al 2012, Shie et al 2015, Plucinska et al 2016. Administration of the Aβ 42 peptide to mice has similar effects by inducing hepatic insulin resistance (Zhang et al 2012(Zhang et al , 2013.…”
Section: Introductionmentioning
confidence: 99%